Pengaruh Pembelajaran PAI Terhadap Kedisiplinan Beribadah Shalat Berjamaah Siswa Kelas VIII di SMPN 1 Sukamakmur Bogor - Mila Aprilia; Puad Hasan; Rendra Fahrurrozie (Advances In Education Journal, 2026)
The lack of student initiative in performing congregational prayers has become the main issue in this research. This research is a quantitative study of an associative descriptive nature aimed at determining the influence of Islamic Religious Education learning on the discipline of congregational prayer among eighth-grade students at SMPN 1 Sukamakmur. From a total population of 144 eighth-grade students, a sample of 106 students was taken using the Slovin formula with a simple random sampling technique. Data collection techniques were carried out through Likert scale questionnaires, observations, interviews, and documentation. Data analysis was conducted using classical assumption tests and simple linear regression. The research results indicate a positive influence of PAI learning on the discipline of congregational prayer with a significance value of 0.000 < 0.05. PAI learning contributes 21.6% to students' prayer discipline. Thus, this research emphasizes that the effectiveness of religious education in the classroom is a crucial factor in shaping the religious character of students.